Peran Dayah sebagai Pusat Pembentukan Pemikiran Ulama Aceh; Transformasi Tradisional ke Modern - Idrus Idrus (Al-Widad, 2025)
The intellectual tradition of dayah in Aceh is expected to be an integrative space between Sufism spirituality and wasathiyah ethics as the foundation of Islamic moderation. However, contemporary reality shows a shift in scholarly orientation due to the influence of modernity and global ideological challenges. This study aims to examine the dialectic between Sufism and wasathiyah in shaping the scholarly character and religious practices of dayah scholars. Using a qualitative approach through a literature review of the works of classical scholars and contemporary sources, this study finds that the dayah Sufism tradition functions not only as spiritual guidance but also as a social ethical system that supports the values of Islamic moderation in Aceh.